Ultrastructure of Rat Rostral Nucleus of the Solitary Tract Terminals in the Parabrachial Nucleus and Medullary Reticular Formation - Park, Sook Kyung; Cho, Yi Sul; Kim, Jong Ho; Kim, Yun Sook; Bae, Yong Chul (Frontiers in Cellular Neuroscience, 2022)
Neurons in the rostral nucleus of the solitary tract (rNST) receive taste information from the tongue, and relay it mainly to the parabrachial nucleus (PBN) and the medullary reticular formation (RF) through two functionally-different neural circuits. To help understand how the information from the rNST neurons is transmitted within these brainstem relay nuclei in the taste pathway, we examined the terminals of the rNST neurons in the PBN and RF by use of anterograde horseradish peroxidase (HRP) labeling, postembedding immunogold staining for glutamate, serial section electron microscopy, and quantitative analysis. Most of the anterogradely-labeled, glutamate-immunopositive axon terminals made a synaptic contact with only a single postsynaptic element in PBN and RF, suggesting that the sensory information from rNST neurons, at the individual terminal level, is not passed to multiple target cells. Labeled terminals were usually presynaptic to distal dendritic shafts in both target nuclei. However, the frequency of labeled terminals that contacted dendritic spines was significantly higher in the PBN than in the RF, and the frequency of labeled terminals that contacted somata or proximal dendrites was significantly higher in the RF than in the PBN. Labeled terminals receiving axoaxonic synapses, which is a morphological substrate for presynaptic modulation frequently found in primary sensory afferents, were not observed. These findings suggest that the sensory information from rNST neurons is processed in a relatively simple manner in both PBN and RF, but in a distinctly different manner in the PBN as opposed to the RF.